2010
DOI: 10.1016/j.juro.2009.12.105
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Heterozygosis on IFN-α Locus is a Prognostic Indicator of Bacillus Calmette-Guerin Response for Nonmuscle Invasive Bladder Cancer

Abstract: This study highlights the predictive value of loss of heterozygosity analysis on interferon-alpha in patients with nonmuscle invasive bladder cancer treated with bacillus Calmette-Guerin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Clinical data indicate that chromosome 9p21 deletions occurred preferentially in larger tumors (>5 cm diameter). Another study has also reported that LOH on IFN-alpha locus at 9p21 is a prognostic indicator of bacillus Calmette-Guerin response for non-muscle invasive bladder cancer [46]. Similarly, Roman et al [47] has investigated the chromosomal aberrations in head and neck squamous cell carcinomas by array CGH and found that the genes involved in cytokine-cytokine receptor interaction pathway were the largest group of genes (23/149) showing chromosomal gains.…”
Section: Discussionmentioning
confidence: 94%
“…Clinical data indicate that chromosome 9p21 deletions occurred preferentially in larger tumors (>5 cm diameter). Another study has also reported that LOH on IFN-alpha locus at 9p21 is a prognostic indicator of bacillus Calmette-Guerin response for non-muscle invasive bladder cancer [46]. Similarly, Roman et al [47] has investigated the chromosomal aberrations in head and neck squamous cell carcinomas by array CGH and found that the genes involved in cytokine-cytokine receptor interaction pathway were the largest group of genes (23/149) showing chromosomal gains.…”
Section: Discussionmentioning
confidence: 94%
“…To our knowledge, only one study has been reported and evaluated the role of loss of heterozygosity (LOH) in the IFN-a (chromosome 9p21) to predict BCG response in patients who underwent TURBT. Results showed that LOH at the IFN-a locus was an independent predictor of BCG response ( p = 0.002) and was significantly associated with increased BCG failure ( p < 0.0001) [7]. …”
Section: Evidence Synthesismentioning
confidence: 99%
“…These alterations included single-nucleotide polymorphisms (SNPs), single-nucleotide variations (SNVs), and mutations [5, 6]. Second, various genetic copy number alterations were associated with bladder cancer [7]. Third, epigenetic regulation of genes, especially by gene methylation, was found to be associated with BCG failure for multiple genes [810].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al demonstrated that BCG increases IL-6 messenger RNA and protein in a time-and dose-dependent manner via an immediate early pathway (12). Furthermore, we highlighted the feasible role of IL-6 and IL-10 ratio (IL-6/IL-10) as a prognostic marker of recurrence in patients affected by NMIBC (9). Urinary interleukins could consequently be used as prognosticators to better assess the outcome of NMIBC patients following BCG therapy.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, the patient failing BCG therapy is a challenge to the urologist and predictors of BCG response should be investigated (2). Although several authors have proposed molecular markers to predict the clinical outcome of patients with non-muscle invasive bladder cancer (NMIBC) following treatment with intravesical BCG (89), no marker has yet proven to be valid in everyday clinical practice (2). Zhang et al demonstrated the induction of cytokine production by BCG, particularly interleukin-6 (IL-6) (10).…”
Section: Introductionmentioning
confidence: 99%